Clinical risk stratification: Prague validation of the DAAE score, a clinical tool for estimating risk of disesase progression in multiple sclerosis - Jelgerhuis, Julia R; Uher, Tomas; Havrdova, Eva Kubala; Horakova, Dana; Schoonheim, Menno M; Fuchs, Tom A (Multiple sclerosis and related disorders, 2025)
BACKGROUND: Secondary progressive MS is associated with a worse prognosis, warranting the need for early predictive tools. The DAAE score estimates the five-year risk of transition to clinical diagnosis of SPMS, showing a 38 % risk in high-risk patients in Amsterdam and Buffalo data. The DAAE score remains to be validated against objective disease progression criteria. METHODS: External validation using data from the Prague MS cohort and MSBase-Lorscheider criteria. RESULTS: Among 2022 patients from the Prague MS database, 14.3 % clinically progressed according to MSbase-Lorscheider criteria over five years. Risk increased with higher DAAE scores comparable to the Amsterdam and Buffalo data; secondary validation showed an AUROC of 0.742 with faster progression for higher risk groups (p < 0.05), therapy-adjusted. CONCLUSION: The DAAE score performs similarly between centers and using objective criteria. These validation steps support its use in personalized MS management and treatment.
Keywords: hodnocení rizik; Male; kohortové studie; Risk Assessment; progrese nemoci; Cohort Studies; Multiple Sclerosis; chronicko-progresivní roztroušená skleróza; prognóza; Adult; dospělí; mužské pohlaví; Disease Progression; Multiple Sclerosis, Chronic Progressive; lidé; ženské pohlaví; Humans; Prognosis; Female; lidé středního věku; roztroušená skleróza; Middle Aged